+0  
 
+1
279
1
avatar+34 

 

Help ASAP step-by-step please So I can understand it.

off-topic
 Mar 25, 2019

Best Answer 

 #1
avatar+30313 
+4

Rearrange the second equation as y = 4 - x.  Substitute this into the first equation:

 

4 - x = x2 - 3x + 4

 

This simplifies to. x2 - 2x = 0

 

This factors as. x(x - 2) = 0, so x = 0 or x = 2

 

Substitute these back into y = 4 - x to find the corresponding values of y.

 Mar 25, 2019
 #1
avatar+30313 
+4
Best Answer

Rearrange the second equation as y = 4 - x.  Substitute this into the first equation:

 

4 - x = x2 - 3x + 4

 

This simplifies to. x2 - 2x = 0

 

This factors as. x(x - 2) = 0, so x = 0 or x = 2

 

Substitute these back into y = 4 - x to find the corresponding values of y.

Alan Mar 25, 2019

13 Online Users

avatar
avatar
avatar
avatar